ANALISIS PENGARUH PRODUK BARU TERHADAP KEPUTUSAN UNTUK MEMBELI PADA PT. DONINDO MENARA UTAMA BANJARMASIN - Susiladewi Susiladewi; Basuki Basuki (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
Increasing population and increasing people's income in Banjarmasin city will increase people's need for comfortable house either as a residence as an investment in the future.The purpose of this study is to know and analyze about new products produced by PT.Donindo Menara Utama Company in relation to the buying decision of the Consumers inhabiting the complex of Metro Indah Housing Banjarmasin.This research is done by taking the object of research that is in Metro Indah Housing Complex which is located at Brig Jend H. Hasan Basri Kayu Tangi BanjarmasinSample amounted to 32 people, taken 10% of the total population of 110 people. Relationship analysis using product moment correlation coefficient sought by the formula of coarse numbers or also called Raw Score method.The result of the research is the coefficient between the new product variables and the decision variable to buy the housing complex of Metro Indah housing owned by PT.Doninda Menara Utama Banjarmasin which is 0.577. The r table for N of 30 with a significant level of 5% is 0.361. The coefficient of correlation of new Product variable with decision variable to buy is greater than correlation value listed in table of product moment r value. It can be concluded that the correlation coefficient of both variables studied is significant or positive.